Association of Pharmacist-Provided Medication Counselingwith Adherence in Outpatients - Samran (Jurnal FARMASIMED (JFM), 2025)
Background: patient medication adherence is critical for therapeutic success. Pharmacist-provided medication counseling can enhance patients' understanding and adherence to treatment regimens. Objective: this study aimed to assess the relationship between pharmacist-provided counseling and medication adherence among outpatients at RSU. Sembiring Delitua. Research Methods: a quantitative study with a cross-sectional design was conducted. A total of 100 outpatients were selected using purposive sampling. Data were collected using a structured questionnaire evaluating counseling quality and adherence through the MMAS-8 scale. The Chi-square test was used for statistical analysis at a significance level of p<0.05. Results: Sixty percent of patients reported receiving counseling, but only 21% received complete counseling. Medication adherence levels showed that 42% had high adherence. Statistical analysis revealed a significant association between medication counseling and adherence (p=0.002), where patients receiving counseling had higher adherence rates. Conclusion: pharmacist-led medication counseling is significantly associated with higher medication adherence among patients. Hospitals are advised to improve the quality and coverage of medication counseling through continuous pharmacist training and the use of supplementary educational media.